2016
DOI: 10.1104/pp.16.01205
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbons Are Essential for Optimal Cell Size, Division, and Growth of Cyanobacteria

Abstract: Cyanobacteria are intricately organized, incorporating an array of internal thylakoid membranes, the site of photosynthesis, into cells no larger than other bacteria. They also synthesize C15-C19 alkanes and alkenes, which results in substantial production of hydrocarbons in the environment. All sequenced cyanobacteria encode hydrocarbon biosynthesis pathways, suggesting an important, undefined physiological role for these compounds. Here, we demonstrate that hydrocarbon-deficient mutants of Synechococcus sp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
67
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 71 publications
5
67
2
1
Order By: Relevance
“…The physiological roles of cyanobacterial hydrocarbons, which are involved in introducing flexibility into membranes and are required for optimal cell division, size, and growth, have been previously reported (7). Though strains harboring the Ols pathway have been proposed to account for a small proportion (approximately 10%) of the cyanobacterial population (4, 5), hydrocarbon production in such strains is recog-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological roles of cyanobacterial hydrocarbons, which are involved in introducing flexibility into membranes and are required for optimal cell division, size, and growth, have been previously reported (7). Though strains harboring the Ols pathway have been proposed to account for a small proportion (approximately 10%) of the cyanobacterial population (4, 5), hydrocarbon production in such strains is recog-…”
Section: Discussionmentioning
confidence: 99%
“…The subcellular location of hydrocarbons is within the lipid bilayers of thylakoid and cytoplasmic membranes, and the biological function of hydrocarbons is thought to be associated with the membrane flexibility required for optimal cell division, size, and growth (7). Free fatty acids in cyanobacteria are thought to be released from complex membrane lipids (8).…”
mentioning
confidence: 99%
“…[10,[14][15][16][17][18][19][20] It is a unicellular coccoid organism, with diameter around 1.6 μm, although this is altered in some mutant strains. [21] Some cyanobacteria, such as Synechococcus elongatus PCC7942, [22,23] which is also commonly used, have more elongated cells. Others, such as Nostoc, [24,25] routinely form filaments.…”
Section: Biological Materialsmentioning
confidence: 99%
“…In addition, isolating membranes via two-phase aqueous polymer partitioning results in considerable losses of cellular material and undersampling of the proteome. Furthermore, both the PM and TM may be heterogeneous (Srivastava et al, 2006;Agarwal et al, 2010;Pisareva et al, 2011) and previous work has suggested that only a hydrocarbon-rich fraction of the TM, and not the whole membrane, is purified via two-phase partitioning (Lea-Smith et al, 2016b). For example, a highly curved 'convergence membrane' substructure in the TM was recently observed, which was in close contact with the PM, and may play a role in biogenesis of thylakoid proteins (Rast et al, 2019).…”
mentioning
confidence: 98%
“…For example, these methods have been shown to give 'purified' PM fractions that actually contain detectable amounts of TM (e.g. Zhang et al, 2015;Lea-Smith et al, 2016b). In addition, isolating membranes via two-phase aqueous polymer partitioning results in considerable losses of cellular material and undersampling of the proteome.…”
mentioning
confidence: 99%